Dietary n-3 PUFA May Attenuate Experimental Colitis - Cloé Charpentier; Ronald Chan; Emmeline Salameh; Khaly Mbodji; Aito Ueno; Moïse Coëffier; Charlène Guérin; Subrata Ghosh; Guillaume Savoye; Rachel Marion-Letellier (Hindawi Limited, 2018)
Background. Inflammatory bowel diseases (IBD) occurred in genetically predisposed people exposed to environmental triggers. Diet has long been suspected to contribute to the development of IBD. Supplementation with n-3 polyunsaturated fatty acids (PUFA) protects against intestinal inflammation in rodent models while clinical trials showed no benefits. We hypothesized that intervention timing is crucial and dietary fatty acid pattern may influence intestinal environment to modify inflammation genesis. The aim of this study was to evaluate the dietary effect of PUFA composition on intestinal inflammation. Methods. Animals received diet varying in their PUFA composition for four weeks before TNBS-induced colitis. Colon inflammatory markers and gut barrier function parameters were assessed. Inflammatory pathway PCR arrays were determined. Results. n-3 diet significantly decreased colon iNOS, COX-2 expression, IL-6 production, and LTB4 production but tended to decrease colon TNFα production (P=0.0617) compared to control diet. Tight junction protein (claudin-1, occludin) expressions and MUC2 and TFF3 mRNA levels were not different among groups. n-9 diet also decreased colon IL-6 production (P<0.05). Conclusions. Dietary n-3 PUFA influence colitis development by attenuating inflammatory markers. Further research is required to better define dietary advice with a scientific rationale.